Nutritional Value Analysis of Carrot Fortified Pempek Prepared with Low Cost Hybrid Temperature Treatment Method as an Alternative Food to Prevent Stunting in Indonesia - Nia Ritonga; A.S. Utami; A Inayatullah; M.T. Handayani; I.G. Riani; U Muharromah (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
The problem of nutritional adequacy remains a major concern in Indonesia. Various measures to reduce stunting rates (one of the effects of malnutrition) have been implemented, including fortifying food products such as iodised salt. This method is considered quite effective in reducing malnutrition problems in Indonesia. Pempek is chosen as a food fortification with a vegetable addition to enhance its nutritional value from a vitamin perspective. The sample was combined with the low cost hybrid temperature method to maintain the nutritional value of pempek. The study used a one-way factorial design to examine how carrot concentration affects the nutritional value of pempek fortification. The analysis carried out were proximate analysis, dietary fiber analysis, and beta-carotene analysis. One-way ANOVA was used for data analysis in SPSS 21.0.0.0; p < 0.05 was considered statistically significant. The fortification of carrot using a combination of an economical, low-cost hybrid temperature treatment method was successfully incorporated into the pempek. The protein and carotene are the main factor to distinguish the best outcome. The best outcome in this research was achieved with sample P2, which included 300 g of carrot in the pempek dough. The results show the significance of the percentages in the proximate and carotenoid perspectives (5.69% and 0.34%, respectively). Contribution to Sustainable Development Goals (SDGs): SDG2: Zero HungerSDG3: Healt and Well-being